(untitled) (Sudurpaschim Spectrum, 2026)
This study analyses the determinants of interest spread and profitability by examining the perception of the bank executives. The study was based on the primary data that were collected from sixteen commercial banks of Nepal. Purposive sampling method was employed while selecting the sample banks and respondents. Both the old and relatively new banks were selected. Online questionnaire was designed and mailed to 153 bank officials and out of mailed questionnaires, only 105 responses were received in usable form. The analysis of primary data was based on frequency distributions, cross-tabulation, and mean ranking score from five point Likert-scale. The purpose of analyzing primary data was to examine the perceived understanding of bank officials in reference to determinants of interest spread and bank profitability in Nepali banking system. The primary data analysis revealed an important role of interest spread in profitability of the banking sector. The results further indicated that management efficiency and bank specific characteristics are the most important factors determining interest spread and profitability of banking sector in Nepal. The findings have important implications to formulate the policy in managing interest spread and profitability of the commercial banks.